Continuous Double Auction Berbasis Web - Feri Krisnanto; Tristiyanto Tristiyanto; Ardiansyah Ardiansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2018)
Sale-purchase often expect the occurrence of mutually fair transaction. Perfect Competition Market is an ideal market structure, because many sellers and buyers will be determined the price based on demand and supply. Continuous Double Auction (CDA) is one method that allows the occurrence of many transactions with the result that buyers get the cheapest price and the seller get a highest price. Currently, transactions can be made online by multiple platforms that promise the information, spacious seller and buyer access, and perfect price competition. CDA method can also be applied to the online market system.This research tries to make e-auction system and simulate that Â market commodities using CDA method, focusing on the indication of price change (price fluctuation) that happened. The quantity of participants who make a sale or buy will also affect the price fluctuation changes. If there are more sellers than the buyer, the market increase (Bullish) and otherwise the market decrease (Bearish). The simulation which applies profit-selling strategy, will increase the price higher than the random simulation.